Plant Bio-resources used in Ethno-veterinary Practices in Jumla District (Nepalese Veterinary Journal, 2017)
Jumla is one of the districts in high mountain region of Nepal from where the medicinal and aromatic plants, their parts and products are exported annually. A study was carried out from March to June 2014 to document the plant resources used in ethno veterinary practice by local people. Focal group discussions and key informant interviews were carried out to enlist plant bio resources used as ethno veterinary medicines. It was revealed that people used 42 plant resources to correct 28 different ailments in animals. Among the listed plant resources, about 87% were the home products of the district. Hence, the study led to the conclusion that there is opportunity to explore the locally found medicinal plants as ethno veterinary medical practice and commercial veterinary herbal medicine.